Study of the Recreational Carrying Capacity of the Caída do Morro Trail (Ilha Grande, Piauí State, Brazil) - de Sousa Melo, Rodrigo; da Costa Silva, Charles; Passos Horta, Brunehilde; de Souza Braga, Solano (Journal of Tourism, Sustainability and Well-being, 2020)
This paper sought to reflect on the methodologies of the carrying capacity assessment in ecotourism trails. After analyzing and defining the methodology presented by Cifuentes (1992) it was possible to estimate the Recreational Carrying Capacity for the "Caída do Morro Trail" in the Tatus community, in the Ilha Grande municipality, state of Piauí, in the Brazilian northeast. For the evaluation of the Recreational Carrying Capacity the specific characteristics of the limiting or correction factors (dune height, trail length and temperature) applied to the control and data collection were used. The method used showed that once an adequate management plan has been implemented with the construction of more support points and acquisition of more equipment by the agencies involved in this activity, the number of visits may increase, but it is also important that visits do not exceed the rate stipulated by the Real Carrying Capacity.